Possibilities of Mathematical Modeling of a Self-Organizing System - Abdullaev U.A (Genius Journals, 2022)
The article focuses on the creation of regression models for forecasting the development of manufacturing enterprises engaged in trade, using information technology, based on self-organizing information systems. The article considers the possibility of developing methods and algorithms to improve the efficiency of the functioning of a self-organizing information system by forecasting and searching for the collection of relevant information. This article aims to show the role of information systems in the trading processes of an enterprise using the method of regression and correlation analysis. Specific mathematical models of nonlinear type have been developed for forecasting and analysis, commercial and private property. Graphical interpretations of the results obtained using the WindowsXP office application are given
Keywords: Regression and correlation analysis; information system; least squares method